2015
DOI: 10.1016/j.jvoice.2014.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Limb Proprioception in Adults With Spasmodic Dysphonia

Abstract: Objectives Focal dystonia of the head, neck are associated with a loss of kinaesthetic acuity at muscles distant from the dystonic sites. That is, while the motor deficits in focal dystonia are confined, the associated somatosensory deficits are generalized. This is the first systematic study to examine, if patients diagnosed with spasmodic dystonia (SD) show somatosensory impairments similar in scope to other forms of focal dystonia. Methods Proprioceptive acuity (ability to discriminate between two stimuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…Recent work from our group demonstrated upper limb proprioceptive deficits in SD 12 . Moreover, studies on the effects of sensory stimulation of the larynx have indicated a reduced inhibition of laryngeal muscle responses to sensory stimulation, i.e., a reduced suppression of motor responses to laryngeal sensory stimulation 5 .…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…Recent work from our group demonstrated upper limb proprioceptive deficits in SD 12 . Moreover, studies on the effects of sensory stimulation of the larynx have indicated a reduced inhibition of laryngeal muscle responses to sensory stimulation, i.e., a reduced suppression of motor responses to laryngeal sensory stimulation 5 .…”
Section: Introductionmentioning
confidence: 75%
“…Abnormal kinaesthetic function has been reported in non-dystonic limbs and muscle systems in SD 12 and other forms of focal dystonia such as blepharospasm and cervical dystonia 10 . This implies that a more generalized somatosensory deficit underlies or is associated with the focal motor dysfunction in dystonia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work by our team had shown a generalized proprioceptive deficit in musician's dystonia (Konczak et al, 2013) and in SD (Konczak et al, 2015). This raises the question if one can identify atypical patterns of somatosensory activation and/or abnormal interaction between somatosensory and motor cortical areas that underlie the observed proprioceptive and motor dysfunction in spasmodic dysphonia.…”
Section: Introductionmentioning
confidence: 87%
“…Furthermore, the perception of arm movement during tonic vibration reflex or during illusory movements induced by vibration in an immobilized arm has been found to be abnormal ( 26 , 27 ) (Table 1 ). Interestingly, proprioceptive acuity has been found to be decreased even in non-dystonic muscles, e.g., in the limb muscles of patients affected by spasmodic dystonia ( 33 ). These sensory abnormalities may impair the process of sensorimotor integration in dystonia.…”
Section: Evidence On Actual and Illusory Proprioceptive Information Pmentioning
confidence: 99%